Michael Bratton og Nicolas van de Walle, Experiments in Africa: Regime Transitions in Comparative Perspective, Cambridge University 1997, 307 s.; Patrick Chabal og Jean-Pascal Daloz, Africa Works: Disorder as Political Instrument, Oxford: The Institutiona - Kjær, Mette; Rudbech, Jens Rudbech (Politica, 2000)
Michael Bratton og Nicolas van de Walle, Experiments in Africa: Regime Transitions in Comparative Perspective, Cambridge University 1997, 307 s.; Patrick Chabal og Jean-Pascal Daloz, Africa Works: Disorder as Political Instrument, Oxford: The Institutional African Institute association with James Curry and Indiana University Press, 1999, 170 s.; Christopher Clapham, Africa in the International The Politics of State Survival, Cambridge: Cambridge University 1996, 340 s.; Aili Mari Tripp, Changing the Rules: The Politics of Liberalization and the Urban Informal in Tanzania, Berkeley: University of California Press, 1997, 2605.